Implementation of Blue Economy Policy in Tourism Sector in Aceh Province - Vellayati Hajad; Ikhsan Ikhsan; Deni Setiawan (Universitas Sebelas Maret, 2024)
Blue economy is a concept about economic activities in or through sea and fresh water. This includes all forms of marine tourism, coastal tourism and freshwater tourism activities, which significantly contribute to sustainable economic practices in the region. The qualitative method has a case study approach with Aceh Province as the research location. The research results show that the blue economy concept is one of the government's solutions to economic and environmental problems. In the process of implementing tourism policies that have a blue economy feel, the Aceh Provincial Government has great authority, which is contained in the Aceh Government's nine authorities, namely establishing a development master plan, coordinating tourism implementation, carrying out registration, recording and data collection on business registration, determining tourism destinations, facilitating promotion of tourism destinations and tourism products, maintaining assets, allocating budgets, forming unique teams to assist agencies. This study concludes that the tourism sector has made a significant contribution to the development of the blue economy concept, so the tourism sector must ensure that tourism-related activities are included in the planning and development of blue economy policies in the tourism sector in Aceh Province, such as minimizing waste, multiplier effect, social inclusion, and innovation and adaptive. This study suggests that the blue economy should be utilized as a conceptual resource so that academics and industry can better connect with the results of neighbouring blue sectors, understand and respond to transformations in blue spaces, and advocate for sustainable tourism in the aquatic world.